Wireless Sensor Network Sebagai Penentu Lokasi Kebakaran Hutan - Rahmad, Iwan Fitrianto; Yusfrizal, Yusfrizal; Tanti, Lili; Triandi, Budi (TIN: Terapan Informatika Nusantara, 2021)
Forests have an important role for living things today. Where the forest is the main source of oxygen for living things. Based on data from the Direktorat Jenderal Planologi Kehutanan dan Tata Lingkungan (PKTL) of the Ministry of Environment and Forestry, it shows that the total forest area of ​​the entire landmass of Indonesia is 94.1 million hectares or 50.1% of the total area. area. land, and about 274,375 hectares burned. In overcoming this problem, the government has taken various ways, ranging from advocating and imposing legal sanctions on individuals and groups who threaten forest sustainability. In the case of forest fires, they are often detected early and get help from the fire department. So the purpose of this research is to carry out early warning of forest fires using NodeMCU. With the help of NodeMCU will provide fast information to find out fires early so that fires can be contained before they spread widely. This technology will provide information on where the fire points are and send that information through the network to the fire monitoring application that is made. To determine location accuracy, the Mamdani fuzzy method is one part of the Fuzzy Inference System which is useful for drawing or making the best decisions in uncertain problems. will be an innovative medium for any fire information in an area so that it quickly and instantly knows the location of the hotspots and directly occurs at the hotspots so that the burning effect is extensive and results in large losses as well as the effects of air pollution that cause large fires